The Phenomenon of Fear of Missing Out Instagram Social Media in Generation Z in the 2024 Presidential Election - Widya Risma Ilahi; Erna Febriani (Jurnal Indonesia Sosial Teknologi, 2024)
In the current digital era, Instagram is not only a place to share personal moments but also a political arena where individuals participate in discussions, campaigns, and other political activities. This research aims to understand the phenomenon of Fear of Missing Out (FoMO) on social media, Instagram, among Generation Z during the 2024 presidential election using Alfred Schutz's phenomenological theory. This research employs the phenomenological method, where data collection techniques used are interviews, observations, and documentation. The study uses an interpretive paradigm to allow the researcher to observe and understand the meanings, values, and behaviors of Generation Z in using Instagram to spread campaign tweets and even comment during the 2024 presidential election. The results of this research show that Generation Z feels a greater desire to use Instagram during the presidential election period. FoMO is a common experience among the informants, particularly related to the fear and anxiety of missing out on important information or discussions happening on Instagram during the 2024 presidential election. The FoMO experienced by the informants indicates a pressure to always stay up-to-date with the latest information, which can negatively impact the informants.